Quantifying efficient information exchange in real network flows - Giulia Bertagnolli (Nature Portfolio, 2021)
While the global efficiency measures how easy it is to travel or exchange information concurrently between any two nodes in a network, this might be difficult to compute when networks are not embedded into space and edge weights do not encode physical distances, but instead represent flows. Here, the authors propose and analyse an efficiency measure based on the flow across least resistance pathways that can be computed without any knowledge on the system except for its weighted representation.